Fault-model of the 2017 Kos-Bodrum (east Aegean Sea) Mw 6.6 earthquake from inversion of seismological and GPS data – Preliminary Report - Saltogianni, Vasso; Taymaz, Tuncay; Yolsal-Çevikbilen, Seda; Eken, Tuna; Gianniou, Michael; Öcalan, Taylan; Pytharouli, Stella; Stiros, Stathis (Zenodo, 2017)
The 20 July 2017 Kos-Bodrum Mw 6.6 normal fault earthquake (AFAD, 2017) at the NW edge of the Quaternary Gökova Bay graben, was a destructive earthquake associated with a small tsunami (Yalciner et al., 2017). In addition, it is the first normal faulting earthquake in the Aegean covered by a dense array of continuous GPS stations which permit a detailed finite fault modeling (FFM). The preliminary seismological evidence (epicenters, hypocenters of the main shock and of the main aftershocks, and focal mechanism of the main shock) deriving from various agencies, data and techniques, indicate a shallow, nearly E-W striking normal faulting, but its details, including its dip (northerly or southerly) are not resolved. On the basis of independent analysis of seismological and geodetic data we obtained Finite Fault Models (FFM), which are very similar and hence describe the “true” fault.
Keywords: ground deformation; coastal uplift/subsidence; TOPological INVersion algorithm (TOPINV); strong motion; earthquake focal mechanism; stochastic equations; earthquake source modeling